GH18 family glycoside hydrolase Chitinase A of Salmonella enhances virulence by facilitating invasion and modulating host immune responses. - Kasturi Chandra; Atish Roy Chowdhury; Ritika Chatterjee; Dipshikha Chakravortty (PLoS Pathogens, 2022)
Salmonella is a facultative intracellular pathogen that has co-evolved with its host and has also developed various strategies to evade the host immune responses. Salmonella recruits an array of virulence factors to escape from host defense mechanisms. Previously chitinase A (chiA) was found to be upregulated in intracellular Salmonella. Although studies show that several structurally similar chitinases and chitin-binding proteins (CBP) of many human pathogens have a profound role in various aspects of pathogenesis, like adhesion, virulence, and immune evasion, the role of chitinase in the intravacuolar pathogen Salmonella has not yet been elucidated. Therefore, we made chromosomal deletions of the chitinase encoding gene (chiA) to study the role of chitinase of Salmonella enterica in the pathogenesis of the serovars, Typhimurium, and Typhi using in vitro cell culture model and two different in vivo hosts. Our data indicate that ChiA removes the terminal sialic acid moiety from the host cell surface, and facilitates the invasion of the pathogen into the epithelial cells. Interestingly we found that the mutant bacteria also quit the Salmonella-containing vacuole and hyper-proliferate in the cytoplasm of the epithelial cells. Further, we found that ChiA aids in reactive nitrogen species (RNS) and reactive oxygen species (ROS) production in the phagocytes, leading to MHCII downregulation followed by suppression of antigen presentation and antibacterial responses. Notably, in the murine host, the mutant shows compromised virulence, leading to immune activation and pathogen clearance. In continuation of the study in C. elegans, Salmonella Typhi ChiA was found to facilitate bacterial attachment to the intestinal epithelium, intestinal colonization, and persistence by downregulating antimicrobial peptides. This study provides new insights on chitinase as an important and novel virulence determinant that helps in immune evasion and increased pathogenesis of Salmonella.